STRATEGI PENGELOLAAN KEUANGAN UMKM DALAM MENGHADAPI ERA TRANSISI PANDEMI COVID 19 - Fitriyana, Mifta; Prasojo, Eko (Journal Competency of Business, 2022)
Financial planning for business actors is important, how in running a business it is necessary to carry out good corporate functions. In a company, management is an important component that must be owned by the company to realize the vision and mission to be achieved, one of which is financial management within the company. Business actors, in this case the focus is on MSMEs, which currently have new challenges, these new challenges emerge of course after the pandemic. With the pandemic, there are a lot of businesses, even business actors "tie their heads" around and continue to survive no matter what so that their business can still exist, because there are not a few MSMEs and even businesses. Various kinds of innovations and creations continue to be improved so that they can still exist in any difficult circumstances. Various analyzes and strategic planning must of course be made in such a way and also not forget to adapt to current conditions. As a business actor, of course, in carrying out the company's main functions, one of which is finance, you must be able to carry it out properly.